1992
DOI: 10.4098/at.arch.92-7
|View full text |Cite
|
Sign up to set email alerts
|

Ram rut-involvement in a hunted population of mouflons

Abstract: . 1992. Ram rut-involvement in a hunted population of mouflons. Acta theriol. 37: 63 -71.This study was conducted during the rut in a protected valley (Vialais) inhabited by one permanent population of ewes. This valley formes part of a larger hunted area. Rams which segregate from ewes entered the Vialais during the pre-rut, first young rams while the oldest rams arrived later. These latter stay in the company of ewes only when most lambs are conceived. The removal of old males shifted the male population str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 17 publications
2
35
0
Order By: Relevance
“…This seems in accord with the mean age of males culled during the last 11 yrs preceding this study. Previous analyses also agreed with this assumption (Bon et al 1992).…”
Section: Discussionsupporting
confidence: 59%
See 4 more Smart Citations
“…This seems in accord with the mean age of males culled during the last 11 yrs preceding this study. Previous analyses also agreed with this assumption (Bon et al 1992).…”
Section: Discussionsupporting
confidence: 59%
“…In a previous paper, we showed that males >7.5 years old entered female ranges later than younger males (Bon et al 1992; Fig. 1).…”
Section: Resultsmentioning
confidence: 58%
See 3 more Smart Citations